LITERACY AND ECONOMIC ACCELERATION THROUGH GREEN ECONOMY IN COASTAL COMMUNITIES - Oryza Sativa Heningtyas; Endang Tri Pujiastuti; Ahmad Basid (Devote: Jurnal Pengabdian Masyarakat Global, 2026)
This community service activity aimed to improve green economy literacy and accelerate the economic activities of coastal communities through the sustainable utilization of local resources. The program was conducted in Pantai Bahagia Village, Muara Gembong District, Bekasi Regency, using participatory and experiential learning approaches. The activities included green economy literacy training, batik-making practice using natural dyes derived from mangrove leaves, group discussions, and post-training assistance. The participants were coastal community members, particularly women involved in micro-scale economic activities. The results showed an improvement in participants’ understanding of green economy concepts, enhanced technical skills in producing environmentally friendly batik products, and increased awareness of sustainable resource management. In addition, participants were able to produce batik products with market value and demonstrated motivation to develop green economy-based businesses. Although there were still limitations in production scale and market access, the program made a tangible contribution to community empowerment and may serve as a replicable model for sustainable economic development in coastal areas.